2022
DOI: 10.3390/brainsci12101295
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Hand Proprioceptive Processing in Paraplegic Individuals with Long-Term Wheelchair Sports Training

Abstract: Previous studies have revealed drastic changes in motor processing in individuals with congenital or acquired limb deficiencies and dysfunction. However, little is known about whether their brains also exhibit characteristic proprioceptive processing. Using functional magnetic resonance imaging, we examined the brain activity characteristics of four individuals with congenital or acquired paraplegia (paraplegic group) who underwent long-term wheelchair sports training, when they passively experienced a right-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…None of the regions showed significantly greater activity in the paraplegic group during the active task. Similarly, no regions showed significantly greater activity in the control group for either task (Morita and Naito 2022).…”
Section: Resultsmentioning
confidence: 85%
“…None of the regions showed significantly greater activity in the paraplegic group during the active task. Similarly, no regions showed significantly greater activity in the control group for either task (Morita and Naito 2022).…”
Section: Resultsmentioning
confidence: 85%
“…The dMRI data were collected from all paraplegic participants but only from 33 control participants. Findings obtained from functional data other than those reported in the present study have been previously reported [33,34]. fMRI and dMRI data were acquired using different 3.0-Tesla MRI scanners (fMRI, MAGNETON Trio Tim, Siemens, Germany; dMRI, Prisma, Siemens, Erlangen, Germany) because, in the institutional setup, the Trio Tim scanner has a broader space for peripheral devices used for motor experiments.…”
Section: General Proceduresmentioning
confidence: 75%